Strategi Komunikasi Pemasaran Terpadu Event JAKCLOTH SUMMER FESTIVAL 2014 “Heroes of Our Time” - ASRIYANI SAGIYANTO (Universitas Muhammadiyah Yogyakarta, 2014)
Technology as communication media and marketing communication are two things which are related to each other. Communication media can become a means to deliver messages to the people as the audience. Rapid technological developments also contribute in familiarizing internet to the society. This phenomenon can be seen from the large number of social networkers that use Facebook for Blackberry, Twitter for IPad, and so forth. The change of people’s behavior which is now more interested to the internet becomes a challenge to the advertising agencies to promote their clients’ products. The agencies are challenged to find the way to make their clients’ product can reach public through different communication media. Similarly, Jakcloth Summer Festival 2014 “Heroes of Our Time” also used social media as one of the integrated marketing communication strategies. It not only can attract people but also can reach the audience as the expected target. Keywords: Event, Communication Media, Integrated Marketing Communication